Beyond the Score: Music as Performance - Cook, Nicholas (New York Oxford University Press, 2013)
First book to explore in detail the idea of music as performanceCook utilizes novel approaches such as computational analysis of phrase archingBased on original research carried at at CHARM (the AHRC Research Centre for the History and Analysis of Recorded Music)In Beyond the Score: Music as Performance, author Nicholas Cook supplants the traditional musicological notion of music as writing, asserting instead that it is as performance that music is loved, understood, and consumed. This book reconceives music as an activity through which meaning is generated in real time, as Cook rethinks familiar assumptions and develops new approaches. Focusing primarily but not exclusively on the Western 'art' tradition, Cook explores perspectives that range from close listening to computational analysis, from ethnography to the study of recordings, and from the social relations constructed through performance to the performing (and listening) body. In doing so, he reveals not only that the notion of music as text has hampered academic understanding of music, but also that it has inhibited performance practices, placing them in a textualist straightjacket.Beyond the Score has a strong historical emphasis, touching on broad developments in twentieth-century performance style and setting them into their larger cultural context. Cook also investigates the relationship between recordings and performance, arguing that we do not experience recordings as mere reproductions of a performance but as performances in their own right. Beyond the Score is a comprehensive exploration of new approaches and methods for the study of music as performance, and will be an invaluable addition to the libraries of music scholars-including musicologists, music theorists, and music cognition scholars-everywhere.Readership: Teachers, researchers and advanced students (graduate and undergraduate) of musicology, music theory, ethnomusicology, and popular music studies. Music Psychologists working on performance. MIR (Music Information Retrieval) specialists. Scholars of interdisciplinary perfomance studies and theater studies. Academically minded performers and PAR (Practice As Research) practitioners. Some general readers with an interest in music.